2000
DOI: 10.1046/j.1365-201x.2000.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycinergic and GABAergic control of intensity-response function of frog ERG waves under different conditions of light stimulation

Abstract: The effect of glycinergic blockade by strychnine and GABAergic blockade by picrotoxin on the intensity-response function and time course of ERG b- and d-wave was investigated in dark and light adapted frog eyecups as well as in chromatically adapted eyecups, in which the responses were predominantly mediated by one photoreceptor type. Both of the blockers markedly increased the maximal response amplitude and thus increased the contrast gain of the mechanisms generating ERG waves. Strychnine but not picrotoxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 52 publications
1
13
1
Order By: Relevance
“…This suggestion is supported by the fact that Herrmann et al (2011) did not obtain any significant effect of the exogenously applied GABA on the operational range of the b-wave responses in wild type mice, although GABA by itself increased their amplitude. All results shown in the present work are in full agreement with our previous results obtained in frog retina, where we have demonstrated that picrotoxin does not alter the dynamic range of the b-wave V-log I function, although it increases the amplitude and slows the time course of the b-and d-waves under photopic conditions of light adaptation (Kupenova, Popova, & Vitanova, 2008;Popova, 2000).…”
Section: Discussionsupporting
confidence: 95%
See 4 more Smart Citations
“…This suggestion is supported by the fact that Herrmann et al (2011) did not obtain any significant effect of the exogenously applied GABA on the operational range of the b-wave responses in wild type mice, although GABA by itself increased their amplitude. All results shown in the present work are in full agreement with our previous results obtained in frog retina, where we have demonstrated that picrotoxin does not alter the dynamic range of the b-wave V-log I function, although it increases the amplitude and slows the time course of the b-and d-waves under photopic conditions of light adaptation (Kupenova, Popova, & Vitanova, 2008;Popova, 2000).…”
Section: Discussionsupporting
confidence: 95%
“…This concentration was chosen among the other tested because it had maximal effect on both the b-and d-wave amplitude (Popova, 2000). The activity of proximal neurons was blocked using N-methyl-D-aspartate (NMDA -Sigma), dissolved in Ringer solution to a concentration of 1 mM.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations